2021
DOI: 10.1097/nmc.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Nurses' Perceptions of Palliative Care in the Neonatal Intensive Care Unit

Abstract: Purpose: Neonatal palliative care is widely endorsed as an essential aspect of neonatal intensive care unit (NICU) practice, yet inconsistencies in its use continue to exist. We examined neonatal nurses' perceptions of barriers and facilitators to palliative care in their NICU setting. Study Design and Methods: A cross-sectional design using the Neonatal Palliative Care Attitude Scale (NiPCAS™©) was administered using an online survey distributed to neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 33 publications
(60 reference statements)
0
22
0
2
Order By: Relevance
“…In addition, an English version, the Iranian version and the Czech version of NiPCAS created other subscales. In Chin et al ( 24 ), subscales of Unite Culture, Resources, and Perceived Inappropriate Care were found after performing EFA. In Forouzi et al ( 26 ), subscales of Insufficient Resources, Inappropriate Personal and Social Attitudes, Inappropriate Organizational Culture, and Inadequate Nursing Proficiency were formed after measuring content validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an English version, the Iranian version and the Czech version of NiPCAS created other subscales. In Chin et al ( 24 ), subscales of Unite Culture, Resources, and Perceived Inappropriate Care were found after performing EFA. In Forouzi et al ( 26 ), subscales of Insufficient Resources, Inappropriate Personal and Social Attitudes, Inappropriate Organizational Culture, and Inadequate Nursing Proficiency were formed after measuring content validity.…”
Section: Discussionmentioning
confidence: 99%
“…Kain ( 21 ) developed the Neonatal Palliative Care Attitude Scale (NiPCAS) to measure nurses' attitudes toward NPC. Psychometric validation of the NiPCAS has also been proven satisfactory in further studies in countries and regions including Australia ( 21 ), United States ( 22 24 ), Italy ( 25 ), Southeast Iran ( 26 ), Czech Republic ( 27 ), Turkey ( 28 , 29 ), Portugal ( 30 ), and Taiwan ( 31 ). In order to explore the attitudes of NICU clinicians in mainland China, Gu and colleagues translated the traditional Chinese version of the NiPCAS into Simplified Chinese ( 32 ).…”
Section: Introductionmentioning
confidence: 90%
“…Additional barriers noted by nurses in the Australian study were: (1) technological imperatives; and (2) lack of ideal physical environment. Among studies on neonatal palliative care completed in the United States (30)(31)(32), participants identified facilitators not mentioned in our study: (1)…”
Section: Comparisonmentioning
confidence: 99%
“…Extant research outside of mainland China has identified the barriers and facilitators that nurses identify in providing neonatal palliative care. Kain in Australia (5), Wright (30), Kyc (31), and Chin (32) in the United States, Cerratti in Italy (33), Chen in Taiwan (34), and Forouzi in Southeast Iran (35) investigated NICU nurses' attitude to neonatal palliative care using the Neonatal Palliative Care Attitude Scale. In addition, Gu explored conditions in mainland China as well (36).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies highlighted the need to enhance nurses' confidence in palliative care and grief through continuing education [6,14,16]. Likewise, to relieve anxiety among healthcare providers, continuing educational training is crucial when providing neonatal palliative care, namely when communicating DNR options with families and pain management for dying neonates [12,13,17,18].…”
Section: Introductionmentioning
confidence: 99%